Formulation-dependent differences in paclitaxel distribution to anatomical sites relevant to chemotherapy-induced peripheral neuropathy - Girdenytė, Milda; Hu, Yang; Ginosyan, Aghavni; Hammarlund-Udenaes, Margareta; Loryan, Irena (Frontiers in Pharmacology, 2024)
Chemotherapy-induced peripheral neuropathy (CIPN) is a dose-limiting adverse event observed in patients receiving paclitaxel, associated with initial pathological changes in the peripheral nervous system, i.e., distal nerves and dorsal root ganglia (DRG). The prevalence of CIPN in patients receiving paclitaxel formulated i) in polyethylated castor oil with ethanol (CreEL-PTX), ii) as albumin-bound (nab-PTX), and iii) in XR17 micelles (micellar-PTX), is unexpectedly varying. We hypothesize that the discrepancy in CIPN prevalence could be governed by differences in the extent of paclitaxel distribution across blood-to-tissue barriers at the CIPN-sites, caused by the specific formulation. The recently developed Combinatory Mapping Approach for CIPN was used to determine the unbound tissue-to-plasma concentration ratio Kp,uu,tissue, after a 4-hour infusion of 4 mg/kg CreEL-PTX, 4 mg/kg nab-PTX or 1 mg/kg micellar-PTX in male and female Sprague Dawley rats. Kp,uu,tissue was determined in conventional (DRG, sciatic nerve) and non-conventional (brain, spinal cord, skeletal muscle) CIPN-sites. Based on our data, the Cremophor-free paclitaxel formulations were associated with a higher distribution of paclitaxel to CIPN-sites than CreEL-PTX, e.g., Kp,uu,DRG of 0.70 and 0.60 for nab-PTX and micellar-PTX, respectively, in comparison to 0.27 for CreEL-PTX (p<0.01). In addition, the fraction of unbound paclitaxel in plasma was on average 1.6-fold higher in nab-and micellar PTX arms and equal to 0.061 and 0.065, respectively, compared to 0.039 for the CreEL-PTX treatment arm (p<0.0001). In the case of similar unbound paclitaxel concentration in the plasma of patients and assumed speciesindependent extent of paclitaxel transport across the barriers, nab-and micellar-PTX formulations can lead to higher paclitaxel exposure at CIPN-sites in comparison to CreEL-PTX.